2019
DOI: 10.1111/ggi.13803
|View full text |Cite
|
Sign up to set email alerts
|

Impact of loss of independence in basic activities of daily living on caregiver burden in patients with Alzheimer's disease: A retrospective cohort study

Abstract: Aim: To investigate the association between decline of basic activities of daily living (ADL) in each dimension and change in caregiver burden in patients with mild-to-moderate Alzheimer's disease.Methods: This retrospective study included 117 outpatients with Alzheimer's disease who presented to the Memory Clinic at the National Center for Geriatrics and Gerontology in Japan between September 2010 and April 2014 (mean age 77.3 AE 6.4 years; 68.6% women). Patients and their caregivers completed comprehensive g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
35
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 28 publications
8
35
0
3
Order By: Relevance
“…Among these eleven, the number of participants at baseline ranged from n = 41 to n = 2014. One study included 41 participants [15], three included between 100 and 200 participants [16][17][18], two studies included between 200 and 300 participants [19,20], and five included more than 300 participants [21][22][23][24][25]. The follow-up ranged from 3 to 36 months.…”
Section: General Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these eleven, the number of participants at baseline ranged from n = 41 to n = 2014. One study included 41 participants [15], three included between 100 and 200 participants [16][17][18], two studies included between 200 and 300 participants [19,20], and five included more than 300 participants [21][22][23][24][25]. The follow-up ranged from 3 to 36 months.…”
Section: General Study Characteristicsmentioning
confidence: 99%
“…The follow-up ranged from 3 to 36 months. One study [25] had a follow up of 3 months, one study [18] had a follow up of 6 months, five studies [15,16,[22][23][24] had a follow up between 12 and 24 months, and four studies [17,[19][20][21] had a follow up of more than 24 months. Of the included studies, eight studies [15,17,18,[21][22][23][24][25] defined the negative impact of caregiving as caregiver burden.…”
Section: General Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the results presented by Kawaharada et al showing that a decline in basic activities of daily living (ADL) among patients with mild-to-moderate Alzheimer's disease increases caregiver burden, after adjusting for behavioral and psychiatric symptoms of dementia and other factors contributing to confusion in patients. 1 We would like to present some discussion points regarding their conclusions.…”
mentioning
confidence: 99%
“…It is noteworthy that Kawaharada et al reported that an ADL decline in feeding (taking a long time to eat or requiring qualified food and feeding assistance) was significantly related to an increased caregiver burden score. 1 Furthermore, the authors showed that in the mild-to-moderate stages, appetite changes and resistive behaviors were oftentimes observed, and considerably increased caregiving time. We agree with this point.…”
mentioning
confidence: 99%